The Influence of Ownership Concentration on Firm Financial Decisions and Value: Evidence from Nairobi Securities Exchange - Muriungi, Anthony; Mwangi, Mirie; Okiro, Kennedy (European Scientific Journal, ESJ, 2021)
This study paper examines the influence of ownership concentration and firm financial decisions on firm value for firms listed on the Nairobi securities exchange. This study is supported by theoretical literature under the signaling hypothesis, institutional monitoring hypothesis, and agency theory. The study used longitudinal data for listed firms during the ten years (2008- 2017) and regression analysis was used to study the nature and extent of the relationship. The target population was sixty-eight firms that traded equity securities during the period. Empirical results reveal that ownership concentration has no significant positive effect on firm value, but dividend payment significantly influences firm value, and the capital structure only compliments other corporate governance processes in a firm. Firms listed on the Nairobi Securities Exchange have a high level of ownership concentration and this suggests, contrary to the shareholder monitoring hypothesis, large shareholders could be entrenched and, unless other complementary corporate mechanisms are present, large shareholders may not act in the best interest of minority shareholders.The youthful spirit of students to become entrepreneurs is apparent to the naked eye. However, the general objective of this research was to analyze the entrepreneurial attitude of male students from the Tecnológico Nacional de México campus, Tepeaca. One hundred and seventy-two male students were surveyed. The questionnaire was designed and validated by experts in the area. The validation was carried out by a new method; This consists of applying a Pearson factorial analysis for linear correlations and chi-square for nonlinear associations. Five postulates are applied to debug and validate each item. The items are taken as factors or independent variables to contrast the working hypotheses. The sampling was random. The results matrix obtained after applying Pearson’s correlation yielded three correlations above 0.7. With these correlations, six linear hypotheses were validated. Only eight chi-squarevalidated nonlinear hypotheses were selected due to the limited space of a scientific article. In general, 400 working hypotheses were designed in the order of 20 items taken in two to two. It is concluded that the surveyed students have extensive knowledge of entrepreneurship. They are prepared for innovation, creation, and success in the companies they own and the companies where they provide their services.